2011
DOI: 10.1177/1721727x1100900104
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Resistance to Canine Leishmaniose is Associated to Polymorphisms of the Canine TNF-α Gene

Abstract: The prevalence of canine leishmaniosis (CanL) infection in an enzootic area is considerably higher than the overall prevalence of the disease, suggesting a role of host genetics related to the outcome of the disease. It is accepted that one determining factor for the outcome of CanL is the type of the triggered immune response, which seems to be genetically determined. TNF-α is a cytokine which plays a crucial role during the immune response against Leishmania parasites. In the present study a case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The inhibition of IL-36 with IL-36RA in human psoriatic skin has been found to ameliorate the inflammatory reactions (20)(21)(22)(23). It has been shown that IL-22, IL-17A, and TNF-a induce the ex vivo production of all three IL-36 by human keratinocytes, whereas IFN-y selectively induces IL-36P (24)(25)(26). In addition, IL-36a and IL-36P, but not IL-36y, directly induce TNF-a mRNA and protein synthesis in keratinocytes demonstrating that IL-36a and IL-36P could regulate TNF-a directly (27)(28)(29).…”
mentioning
confidence: 99%
“…The inhibition of IL-36 with IL-36RA in human psoriatic skin has been found to ameliorate the inflammatory reactions (20)(21)(22)(23). It has been shown that IL-22, IL-17A, and TNF-a induce the ex vivo production of all three IL-36 by human keratinocytes, whereas IFN-y selectively induces IL-36P (24)(25)(26). In addition, IL-36a and IL-36P, but not IL-36y, directly induce TNF-a mRNA and protein synthesis in keratinocytes demonstrating that IL-36a and IL-36P could regulate TNF-a directly (27)(28)(29).…”
mentioning
confidence: 99%
“…A correlation of two SNPs, i.e. TNF-α -40 C/Α and TNF-α -1243 C/G, located upstream the canine TNF-α open reading frame with susceptibility or resistance to CanL, respectively, was determined from a study of naturally infected dogs in Greece [6].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the failure to control infection is related to the Th2 immune response, increased activity of humoral immunity and the production of IL-4, IL-5, IL-6, IL-10 and IL-13 [4]. Other genetic factors, such as major histocompatibility complex (MHC) class II and TNF-α have been analyzed for CanL and signifi cant correlations have been reported [5,6]. SLC11A1 (Solute Carrier Family 11 member 1), also known as Nramp1 (Natural resistance associated macrophage protein 1), is a metal ion transporter protein, which is expressed in the lysosomal compartment of professional phagocytes [7].…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 is capable to regulate several cytokines including IL-8, TNF-alpha, VEGF and possibly other cytokines (IL-37) (unpublished data), suggesting a possible role of this newly cytokine in the inflammatory response and recruitment of inflammatory cells. This effect, may involve this new protein in several autoimmune diseases where cytokines/chemokines play an important and active role (22)(23)(24).…”
mentioning
confidence: 98%